2014
DOI: 10.1111/acel.12223
|View full text |Cite
|
Sign up to set email alerts
|

Aging impairs peritoneal but not bone marrow‐derived macrophage phagocytosis

Abstract: Aging results in deterioration of the immune system, which is associated with increased susceptibility to infection and impaired wound healing in the elderly. Phagocytosis is an essential process in both wound healing and immune defence. As such, age-related impairments in phagocytosis impact on the health of the elderly population. Phagocytic efficiency in peritoneal macrophages, bone marrow-derived macrophages and bone marrow monocytes from young and old mice was investigated. Aging significantly impaired ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 41 publications
9
117
0
2
Order By: Relevance
“…We demonstrated that this impairment was due to age-related changes in the microenvironment in the peritoneum and not intrinsic defects in macrophages. As such, we suggest that defects may be reversible and macrophages could be targeted therapeutically in order to boost immune function in the elderly [96]. One potential area of controversy in murine studies is the age of young and old mice.…”
Section: Macrophage Phagocytosismentioning
confidence: 97%
“…We demonstrated that this impairment was due to age-related changes in the microenvironment in the peritoneum and not intrinsic defects in macrophages. As such, we suggest that defects may be reversible and macrophages could be targeted therapeutically in order to boost immune function in the elderly [96]. One potential area of controversy in murine studies is the age of young and old mice.…”
Section: Macrophage Phagocytosismentioning
confidence: 97%
“…Studies on peripheral immunity have shown a loss of phagocytic capacity and function in macrophages with age (Plowden et al 2004), although this result is not consistent across all studies (Gardner et al 1981) and may differ between inflammatory cell types (Linehan et al 2014). Cultured macrophages from aged humans have a diminished phagocytic capacity for myelin debris (Natrajan et al 2015), and in vivo studies have shown that the rate of remyelination is reduced in aged rodents but can be restored with an infusion of monocytes from young animals (Ruckh et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of sepsis-induced heart failure have been rised concerns both in basic and clinic research. An ample of molecular mechanisms such as apoptosis, immune regulation, mitochondria, and energy metabolism have been revealed [1113]. Autophagy is associated with accelerated cardiac aging.…”
Section: Introductionmentioning
confidence: 99%